Pengaruh Model Pembelajaran Experiential Learning Terhadap Keterampilan Menulis Bahasa Inggris Mahasiswa PGSD Universitas Muhammadiyah Tangerang - Wulandari, Ratih Ayu; Rosnaningsih, Asih (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
Writing is one of the productive skills that require precision and perseverance. In the learning process, students often find it difficult to learn to write. Experiential Learning is a student-centered learning method that emphasizes learning experience. The purpose of this study was to determine the effect of the use of Experiential Learning model on English students’ writing skills in the fourth semester of Teacher Elementary Education of University of Muhammadiyah Tangerang. This research used a quantitative approach with a quasi-experimental design method. The instrument used in this study was a descriptive essay writing test. The results showed: (1) the results of the pretest t-count 2,319> t-table 2,000 or H1 were accepted, namely there were differences in writing skills between the control class and the experimental class, (2) the results of the posttest t-count 2,319> t-table 2,000 or H1 were accepted or there were differences in writing skills between control classes and experimental class after being given the Experiential Learning model. It can be concluded that by employing the Experiential Learning model, students can get maximum writing results because though this learning model, students can reflect the knowledge they have during the learning process of writing